Crafting the Tourism Green Mosaic: Sustainable Community Tourism Insights Drawn from Grounded Revelations from the Sri Lankan Landscape - Suduweli Kondage Lathisha Jayangi Ramanayaka (NHI HOSPITALITY INTERNATIONAL JOURNAL, 2024)
Purpose of the study: This study explores how sustainable community tourism drives socioeconomic development through active community involvement, focusing on alternative livelihoods and participatory resource management to foster inclusive, grassroots-led growth. Design/methodology: A qualitative multiple case study design was employed, using in-depth interviews conducted in two phases for longitudinal insights into community tourism dynamics in Sri Lanka. Findings: Three key propositions emerged, revealing how community participation and sustainable practices interlink to shape tourism outcomes, highlighting successes, challenges, and local engagement impacts. Research limitations/Implications: Findings apply to community tourism in Sri Lanka and similar developing contexts, offering theoretical and managerial insights for Community Environmental and Tourism Initiatives (CETIs) and sustainable development strategies. Novelty/Originality of the study: The study introduces a green mosaic framework, advancing knowledge by integrating environmental sustainability with community empowerment to redefine tourism-led socioeconomic development.